Content curation with social media in libraries - Guallar, Javier (Anuario ThinkEPI, 2016)
An analysis of how libraries curate content in social media platforms is discussed. The social media platforms that are analyzed are include Scoop.it, Paper.li, Flipboard, Storify, Milq, List.ly, Facebook, and Twitter; numerous examples are provided.